Material a base de almidón de maíz más concepto de progresividad, para el desarrollo de una vivienda rural en el cantón Gonzanamá - Piedra Sánchez, Gonzalo Roberto (2018)
Abstract:In order to achieve the double objective, both to take advantage of local materials for the construction of rural housing in Gonzanamá canton, and to help reduce the increasing environmental pollution, the present investigation was oriented to the study of the physical and mechanical characteristics of a new ecological construction material, previously investigated, obtained from corn starch. The material studied consists of a mixture of one part of corn starch, five parts of sand (dosage of 1: 5) and 16.66% water (optimum content), which hardens after a process of cooking in an oven of microwave. In the first phase, the work consisted in the extraction of corn starch, the preparation of the mixture and the obtaining of the hardened material, in which its resistance was verified by physical and mechanical tests, whose results are presented and discussed. Then, we proceeded to the design of a typical rural housing using the new material, which can be built in different stages, according to both, the economic possibilities of families and the production of corn on their land.